EFEKTIVITAS MODUL PEMBELAJARAN MATEMATIKA BERBASIS ELEKTRONIK DALAM MENINGKATKAN KEMAMPUAN LITERASI NUMERASI SISWA - Huda, Nuril; Afidatuzzaro, Nurul; Sujarwo, Imam; Sari, Sulistya Umie Ruhmana (Universitas Bhinneka PGRI, 2024)
This research focuses on examining the level of effectiveness of mathematics learning e-modules in improving students' abilities in the field of numeracy literacy, especially at the initial level in the secondary school years. Based on the quasi-experimental design used and then using the one group pretest-posttest formula, this research is included in the experimental category. The population group for this study were grade 7 students at SMP Negeri 13 Malang, and the sample consisted of 20 grade 7A students. The sampling technique used is purposive non probability type. Quantitative data in this research was collected through tests using pretest and posttest sheets. Data analysis was carried out using a paired t-test using the SPSS program and the gain value formula. Based on the research results, it is known that the t-test significance level is 0.002, which means that the significance value is less than 0.05. As for the calculation of the gain value, the result was 0.4 or equivalent to the medium level effective category. So it is concluded that the e-learning module is effective in improving students' abilities in the numeracy literacy aspect.